Protection levels of vaccinated pigeons (Columba livia) against a highly pathogenic newcastle disease virus strain - Carrasco, Adriano O. T.; Seki, Meire C. [UNESP]; de Sousa, Ricardo L. M. [UNESP]; Raso, Tania F.; Pinto, Aramis A. [UNESP] (Springer, 2009)
The purposes of this study were to model a vaccination regimen for Newcastle disease virus (NDV) in pigeons, and to evaluate the susceptibility and behavior of vaccinated birds against a highly pathogenic NDV Brazilian strain. Antibody response was assessed by means of hemagglutination inhibition test (HI), and viral genome excretion by means of RT-PCR. Vaccinal strains (La Sota and Ulster) induced high antibody titers without any adverse effects, both in inoculated and in sentinel birds. A viral strain pathogenic for chickens did not produce clinical signs of the disease in experimentally infected pigeons. Only 4 out of 10 vaccinated pigeons shed NDV genome, and just for two days. Results confirmed the high infectivity of the vaccinal strains used, as all nonvaccinated pigeons showed antibody titers as high as those of vaccinated birds.
Keywords: Newcastle disease virus; Pigeon; Columba livia; Serology; Experimental infection; Vaccination; RT-PCR